2018
DOI: 10.1186/s12916-017-0997-z
|View full text |Cite|
|
Sign up to set email alerts
|

Built environmental characteristics and diabetes: a systematic review and meta-analysis

Abstract: BackgroundThe built environment influences behaviour, like physical activity, diet and sleep, which affects the risk of type 2 diabetes mellitus (T2DM). This study systematically reviewed and meta-analysed evidence on the association between built environmental characteristics related to lifestyle behaviour and T2DM risk/prevalence, worldwide.MethodsWe systematically searched PubMed, EMBASE.com and Web of Science from their inception to 6 June 2017. Studies were included with adult populations (>18 years), T2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
4
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(121 citation statements)
references
References 118 publications
(155 reference statements)
3
109
4
5
Order By: Relevance
“…13,14 Sedentary lifestyles and consumption of energydense and processed food that is rich in fats and sugars both constitute major risk factors of type 2 diabetes. 15 Un healthy diet has emerged as one of the primary causes in the develop ment of chronic disease, particularly type 2 diabetes. 16 Exposure to the local food environment has been shown to be associated with dietary behaviour and the quality of dietary intake 17 and implicated in the prevalence and sociospatial distribution of obes ity, 18 gestational diabetes, 19,20 and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Sedentary lifestyles and consumption of energydense and processed food that is rich in fats and sugars both constitute major risk factors of type 2 diabetes. 15 Un healthy diet has emerged as one of the primary causes in the develop ment of chronic disease, particularly type 2 diabetes. 16 Exposure to the local food environment has been shown to be associated with dietary behaviour and the quality of dietary intake 17 and implicated in the prevalence and sociospatial distribution of obes ity, 18 gestational diabetes, 19,20 and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…16 Exposure to the local food environment has been shown to be associated with dietary behaviour and the quality of dietary intake 17 and implicated in the prevalence and sociospatial distribution of obes ity, 18 gestational diabetes, 19,20 and type 2 diabetes. 15 Previous studies 21 have relied on geographical information system (GIS)-based measures of accessibility to food environments, expressed in terms of objective measures of proximity and density and as the proportion of unhealthy food environments to the total food supply environments within geographically defined neighbourhoods. Un healthy food-supply environments generally comprise retail outlets that sell high-calorie and processed foods, soft drinks, alcohol, and other beverages-ie, products rich in saturated fat, salt, sugar, and other ingredients that are harmful to health.…”
Section: Introductionmentioning
confidence: 99%
“…Jones and colleagues (68) analyzed North Carolina, New York, and Maryland census data and found an increased likelihood of availability of recreational facilities and parks in predominantly non-Hispanic white neighborhoods compared with ethnic minority neighborhoods (i.e., predominantly black and Hispanic neighborhoods). Den Braver and colleagues (40) reported that living in an urban residence was associated with higher T2DM risk or prevalence compared with living in a rural residence; higher neighborhood walkability and more green space tended to be associated with lower T2DM risk or prevalence. Several other reviews noted the role of adequate housing in overall health and well-being (23,130,131); one reported that housing instability and unmet material needs were associated with increased risk of diabetes and poorer outcomes among diabetes patients (14).…”
Section: Living and Working Conditionsmentioning
confidence: 99%
“…For example, a recent meta-analysis of observational studies indicated that highly walkable neighbourhoodsi.e. neighbourhoods featuring characteristics that promote walkingare associated with lower risk of type 2 diabetes [6]. Gaining insight into characteristics related to car driving can help inform transport-policies, and thereby improve health and outcomes such as traffic safety, air quality, congestion and climate change.…”
Section: Introductionmentioning
confidence: 99%